Hybrids, identity and knowledge boundaries: Creative artists between academic and practitioner communities. (June 2020) - Lam, Alice
Hybrid people can be riven by identity conflicts and yet be profoundly disruptive of social boundaries. How can we understand these two facets of hybridity? This study examines how internal identity conflict resolution is related to external boundary disruption by focusing on the identity work of individuals who cross professional knowledge boundaries. It looks at artist-academic hybrids who operate at the interface between the academic and art worlds. The analysis shows the dynamic interplay between their hybrid identity work and knowledge boundary work. It distinguishes three categories of hybrids ('Janusian', 'ambivalent' and 'asymmetric') whose varied identity work strategies ('integrative', 'multiplex' and 'buffering') disrupt knowledge boundaries in different ways ('blurring', 'transgressing' and 'brokering'). The study sheds light on the varied nature of hybrids and the mutually constitutive nature of their internal and external identity work. It advances our understanding of identity work as an agentic activity and reveals the identity processes underlying the disruption of knowledge boundaries.